Vertical distribution of living ostracods in deep-sea sediments, North Atlantic Ocean. (April 2017) - Jöst, Anna B.; Yasuhara, Moriaki; Okahashi, Hisayo; Ostmann, Alexandra; Arbizu, Pedro Martínez; Brix, Saskia
Abstract: The depth distribution of living specimens of deep-sea benthic ostracods (small crustaceans with calcareous shells that are preserved as microfossils) in sediments is poorly understood, despite the importance of this aspect of basic ostracod biology for paleoecologic and paleoceanographic interpretations. Here, we investigated living benthic ostracod specimens from deep-sea multiple core samples, to reveal their depths distributions within sediment cores. The results showed shallow distribution and low population density of living deep-sea benthic ostracods (which are mostly composed of Podocopa). The living specimens are concentrated in the top 1 cm of the sediment, hence deep-sea benthic ostracods are either epifauna or shallow infauna. This observation is consistent with the information from shallow-water species. We also confirmed shallow infaunal (0.5–2 cm) and very shallow infaunal (0–1 cm) habitats of the deep-sea ostracod genera Krithe and Argilloecia, respectively. Highlights: Deep-sea benthic ostracods show generally low living population densities. Living benthic ostracods show shallow vertical distribution in deep-sea sediments. Infaunal nature of genus Krithe Brady, Crosskey & Robertson, 1874 was confirmed. Argilloecia Sars, 1866 may be very shallow infauna.